Perancangan Sistem Informasi Penjualan Tunai pada Bread’O Bakery Berbasis Website Menggunakan PHP dan MySQL - Diniyanti Agustin; Roni Anagora (ALMUISY: Journal of Al Muslim Information System, 2025)
A sales information system is a collection of procedures that hold information on two or more parties transaction activities and can be used to achieve certain goals. In this scenario, the Bread'O Bakery business was picked as a research location since the sales information system in that location is poorly maintained, resulting in frequent problems in registering transactions and generating sales reports. The goal of this research is to make it easier for shop managers to receive actual and correct data so that they may improve business performance without having to record manually, which takes a long time. Keywords: Information System, Cash Sales, PHP, MySQL